Application method of electrolytic aluminum fluorine-containing waste residue

By replacing sodium fluoride with fluorine waste slag, the low production efficiency and high cost problems caused by high aluminum content in lithium iron phosphate battery powder recycling are solved, efficient extraction of lithium and industrial-grade production of lithium carbonate are achieved, and production costs are reduced .

CN119461424APending Publication Date: 2025-02-18GUIYANG JINHUI SIYUAN RENEWABLE RESOURCES RECYCLING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411666396.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the recycling process of lithium iron phosphate battery powder, the high aluminum content causes frequent gas emission of the leaching liquid, which affects production efficiency, and the use of sodium fluoride to remove aluminum is high, which increases the production cost of iron phosphate.

Method used

Fluorinated waste residue is used instead of sodium fluoride, and industrial-grade lithium carbonate is prepared by activating the fluorinated waste residue and reacting with the leaching solution of lithium iron phosphate battery powder, removing aluminum and extracting lithium.

Benefits of technology

It effectively reduces the processing cost of iron phosphate, realizes efficient extraction of lithium and industrial-grade production of lithium carbonate, and improves the recycling efficiency of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461424A_ABST
    Figure CN119461424A_ABST
Patent Text Reader

Abstract

The invention relates to an application method of electrolytic aluminum fluorine-containing waste residues. The method comprises the following steps: preparing a sodium hydroxide solution, adding fluorine-containing waste residue powder into the solution, activating for 1-2 hours, filtering to obtain activated residues, and measuring the moisture and fluorine content of the activated residues; dissolving the lithium iron phosphate battery powder with sulfuric acid, and filtering to obtain carbon powder and leachate; adding sodium carbonate into the leachate to control the pH value of the leachate to be 1.5-2, adding activated slag, and stirring to remove aluminum; filtering the aluminum-removed slurry to obtain purified liquid and aluminum-removed slag, adding an oxidizing agent into the purified liquid to prepare iron phosphate, and taking iron phosphate synthesis mother liquor as an acidic lithium sulfate solution 1; leaching the aluminum-removed slag by adopting sulfuric acid, removing fluorine by adopting calcium carbonate, filtering to obtain a lithium sulfate solution 2 and tailings, and feeding the tailings to a cement plant as a cement raw material; mixing the lithium sulfate solution 1 and the lithium sulfate solution 2, removing impurities again, and enabling the purified solution to enter an MVR concentration system to obtain a lithium sulfate solution with the lithium concentration of 15-20g / L; and adding sodium carbonate into the lithium sulfate solution, stirring and precipitating lithium, and filtering to obtain a lithium carbonate product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of comprehensive recycling of waste materials, and relates to a technical method for applying lithium-containing overhaul slag to comprehensive recycling of lithium iron phosphate battery powder. Background Art

[0002] It is estimated that the scale of retired lithium iron phosphate power batteries in my country will reach 1.531 million tons in 2030. At present, the recycling of retired batteries mainly adopts dismantling and crushing components to separate metal shells, aluminum foil, copper foil and positive and negative electrode mixed powder, among which the mixed powder is also called battery powder. After the battery has gone through the charge and discharge cycle, the aluminum foil is corroded to a certain extent. In addition, the contact with air after crushing causes the weathering toughness of the aluminum foil to decrease and it is not easy to separate from the battery powder. To ensure the yield of positive and negative electrode materials in the crushing process, the aluminum content in the powder should not be less than 2.5%, or even higher. When the aluminum content is higher than a certain value, in the wet recovery and acid leaching process, a large amount of hydrogen is generated due to the dissolution of aluminum, resulting in frequent leaching tanks, which seriously affects production efficiency. In addition, in the comprehensive recovery of iron phosphate, aluminum will enter the iron phosphate product as impurity ions, which seriously affects the quality of iron phosphate. At present, sodium fluoride is added to the leachate to precipitate the aluminum complex into aluminum fluoride and sodium hexafluoroaluminate. However, sodium fluoride is expensive, 5,000 yuan per ton. The cost of sodium fluoride consumed in one ton of iron phosphate is more than 1,500 yuan. The rising cost of iron phosphate reduces the economic efficiency of comprehensive recycling of battery powder.

[0003] The present invention adopts fluorine-containing waste slag to replace sodium fluoride for aluminum removal, which can not only greatly reduce the processing cost of iron phosphate, but also extract lithium from the overhaul slag to prepare industrial-grade lithium carbonate, thereby realizing effective utilization of resources.

[0004] Table 1 Main chemical components of fluorine-containing waste slag from electrolytic aluminum element(%) Li F Na <![CDATA[Al2O3]]> K CaO MgO Si Fe C Ni Waste 1.26 20.25 11.81 12.21 0.96 5.54 2.12 8.98 1.31 5.02 0.32 Table 2 Main chemical components of battery powder element(%) LiFePO4 LiF Al Cu Ni Co Mn Si Ca C Cr Battery powder 52 1.5 2.6 0.5 0.1 0.08 0.15 0.05 0.05 35 0.02 Summary of the invention

[0005] The present invention adopts fluorine-containing waste residue to replace sodium fluoride to remove fluorine from lithium iron phosphate battery powder leachate, and simultaneously performs leaching and lithium extraction to prepare industrial-grade lithium carbonate.

[0006] 1) Prepare sodium hydroxide solution first, add fluorine-containing waste slag powder into the solution for activation for 1-2 hours, filter to obtain activated slag and filtrate, measure the moisture and dry basis fluorine content of the activated slag, and reuse the filtrate to activate the next batch of overhaul slag; 2) The lithium iron phosphate battery powder is completely dissolved in sulfuric acid, and the carbon powder and leachate are obtained by filtration; 3) Control the pH of the leaching solution between 1.5 and 2 by adding sodium carbonate, and add a certain amount of activated slag for stirring to remove aluminum; 4) The aluminum removal slurry is filtered to obtain a purified liquid and aluminum removal slag. An oxidant is added to the purified liquid under certain conditions to prepare iron phosphate. The synthetic mother liquor of iron phosphate is mainly an acidic lithium sulfate solution 1 with a lithium concentration of 5-8 g / L; 5) The aluminum slag is leached with sulfuric acid, and the fluorine is removed with calcium carbonate. The lithium sulfate solution 2 and tailings are filtered out. The lithium concentration of the lithium sulfate solution 2 is 4-7g / L. The tailings are sent to the cement plant as cement raw materials; 6) Lithium sulfate solution 1 and lithium sulfate solution 2 are mixed and impurities are removed again, and the impurity-removed purified liquid enters the MVR concentration system to separate sodium sulfate salt and lithium sulfate solution with a lithium concentration of 15-20g / L; 7) Add a certain amount of sodium carbonate to the lithium sulfate solution to stir and precipitate lithium, filter to obtain lithium carbonate product and lithium-containing sodium sulfate solution, and return the lithium-containing sodium sulfate solution to the MVR for further concentration.

[0007] 8) The method for applying the fluorine-containing waste slag from electrolytic aluminum according to claim 1, characterized in that the fluorine-containing waste slag is a mixture of one or more of electrolytic aluminum overhaul slag, carbon slag, and electrolyte; the lithium content is 1-3%, the fluorine content is 20-40%, the aluminum content is 8-15%, and the fineness is above 150 mesh; 9) The method for applying fluorine-containing waste slag from electrolytic aluminum according to claim 1, characterized in that the activation solid-liquid ratio of the overhaul slag is 1:(1-3), the concentration of sodium hydroxide is 5-15%, the activation temperature is 60-80°C, and the activation time is 1-3h; 10) The method for using fluorine-containing waste slag from electrolytic aluminum according to claim 1, characterized in that the solid-liquid ratio of lithium iron phosphate battery powder leaching is 1:(3-5), the leaching end point pH is 0.5-1.5, the leaching time is 2-5h, and the leaching temperature is 40-80°C; 11) The method for applying fluorine-containing waste slag from electrolytic aluminum according to claim 1 is characterized in that the amount of aluminum removal from the activated slag is added according to the ratio of fluorine to aluminum, the mass ratio of total fluorine in the activated slag to total aluminum in the battery powder leachate is (3-5):1, the typical aluminum concentration of the leachate is 3-5g / L, which is less than 0.15g / L after aluminum removal, and the aluminum removal efficiency is greater than 95%; 12) The method for using fluorine-containing waste slag from electrolytic aluminum according to claim 1, characterized in that the solid-liquid ratio of sulfuric acid leaching to remove aluminum slag is 1:(2-4), the leaching end point pH is 0.5-1.5, the leaching time is 2-5h, and the leaching temperature is 60-100°C; 13) The method for applying fluorine-containing waste slag from electrolytic aluminum according to claim 1 is characterized in that the temperature of the sodium carbonate lithium precipitation process is 90-95°C, 200-300g / L of sodium carbonate solution is added, and the obtained lithium carbonate meets industrial grade standards.

[0008] The method of the present invention has the following advantages: 1. Turn waste into treasure and recycle resources; 2. Significantly reduce the processing cost of recycling iron phosphate from battery powder; 3. Extract lithium from overhaul slag to synthesize industrial-grade lithium carbonate in one step, reducing purification costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 The present invention is a process flow chart of a method for utilizing fluorine-containing waste slag from electrolytic aluminum. DETAILED DESCRIPTION

[0010] The present invention is further described below in conjunction with the examples, which are merely further supplements and explanations of the present invention, rather than limitations of the invention.

[0011] Example 1 Weigh 150kg of caustic soda flakes, add 1.5m³ of water and stir to dissolve, add 750kg of fluorine-containing waste residue (lithium content 1.25%, fluorine content 22%, aluminum content 12%, mesh size 200), and heat to 80℃ for activation for 2h. Filter to obtain 900kg of activated slag (water content 35%, dry basis fluorine content 25.5%). Weigh 2000kg of lithium iron phosphate battery powder (lithium content 2.2%, aluminum content 2.5%), add 6m³ of water to make slurry, add 1000kg of 98% sulfuric acid under stirring and stir to leach for 2h. The process is controlled by adding sulfuric acid to pH 1, and the temperature is 60-70℃. Filter and wash to obtain 1150kg of wet carbon powder (water content 50-55%), 6.2m³ of leached filtrate, lithium content 6.5g / L, aluminum content 5.4g / L. The pH of the leaching solution was adjusted to 1.5-1.6, and 800 kg of activated wet slag was added. The temperature was controlled at 60 ° C, and the reaction was stirred for 1 hour. 1200 kg of aluminum removal slag and 6 m³ of purified liquid were filtered to obtain the aluminum content of 0.125 g / L. Under the stirring condition of the purified liquid, an excess of 27.5% hydrogen peroxide was slowly added to the purified liquid to synthesize dihydrate iron phosphate. The synthetic mother liquor was lithium sulfate solution 1 with a lithium concentration of 5.8 g / L. 2200 kg of water and 500 kg of sulfuric acid were added to the aluminum removal slag for stirring and leaching. The leaching temperature was 85 ° C, the leaching time was 2 hours, the end point pH was 0.8, and calcium carbonate was added to adjust the pH to 5-5.5 for defluorination. The leaching slag and lithium sulfate solution 2 were filtered and washed to obtain the leaching slag with a lithium concentration of 4.8 g / L. Under the mixing condition of lithium sulfate solution 1 and lithium sulfate solution 2, sodium hydroxide was added to adjust the pH to 10 for weight removal, and then the solution was injected into the MVR concentration system. The lithium concentration of the liquid was 18 g / L. 250 g / L sodium carbonate solution was prepared according to the lithium carbonate equivalent, and slowly added into the concentrated lithium sulfate solution. The temperature was controlled at 92°C. After the sodium carbonate solution was added, the reaction was continued for 30 min. The slurry was centrifuged and washed to obtain lithium carbonate. The purity of lithium carbonate was tested to be 99.35%, which met the industrial grade requirements.

[0012] Example 2 Weigh 200kg of caustic soda flakes, add 3m³ of water and stir to dissolve, add 1000kg of fluorine-containing waste residue (lithium content 1.25%, fluorine content 22%, aluminum content 12%, mesh size 150), heat to 80℃ and activate for 2h. Filter to obtain 1100kg of activated slag (water content 30%, dry basis fluorine content 27.3%). Weigh 2000kg of lithium iron phosphate battery powder (lithium content 2.2%, aluminum content 2.5%), add 6m³ of water to make slurry, add 1000kg of 98% sulfuric acid under stirring and stir to leach for 2h. The process is controlled by adding sulfuric acid to pH 1, and the temperature is 60-70℃. Filter and wash to obtain 1150kg of wet carbon powder (water content 50-55%), 6.2m³ of leached filtrate, lithium content 6.4g / L, aluminum content 5.1g / L. The pH of the leaching solution was adjusted to 1.5-1.6, and 620 kg of activated wet slag was added. The temperature was controlled at 60 ° C, and the reaction was stirred for 1 hour. 1100 kg of aluminum removal slag and 6 m³ of purified liquid were filtered, and the aluminum content of the purified liquid was 0.102 g / L. Under stirring conditions, an excess of 27.5% hydrogen peroxide was slowly added to the purified liquid to synthesize dihydrate iron phosphate. The synthetic mother liquor was lithium sulfate solution 1 with a lithium concentration of 5.8 g / L. 2200 kg of water and 450 kg of sulfuric acid were added to the aluminum removal slag for stirring and leaching. The leaching temperature was 85 ° C, the leaching time was 2 hours, the end point pH was 1, and calcium carbonate was added to adjust the pH to 5-5.5 for defluorination. The leaching slag and lithium sulfate solution 2 were filtered and washed to obtain the leaching slag with a lithium concentration of 4.5 g / L. Under the mixing conditions of lithium sulfate solution 1 and lithium sulfate solution 2, sodium hydroxide was added to adjust the pH to 10 for weight removal, and then the solution was injected into the MVR concentration system. The lithium concentration of the liquid was 18 g / L. 250 g / L sodium carbonate solution was prepared according to the lithium carbonate equivalent, and slowly added into the concentrated lithium sulfate solution. The temperature was controlled at 92°C. After the sodium carbonate solution was added, the reaction was continued for 30 min. The slurry was centrifuged and washed to obtain lithium carbonate. The purity of lithium carbonate was tested to be 99.21%, which met the industrial grade requirements.

[0013] Comparative Example 1 Weigh 2000kg of lithium iron phosphate battery powder (lithium content 2.2%, aluminum content 2.5%), add 6m³ of water to make a slurry, add 1000kg of 98% sulfuric acid under stirring and stir for leaching for 2h. The process is controlled by adding sulfuric acid to pH 1 and the temperature is 60-70℃. Filter and wash to obtain 1150kg of wet carbon powder (water content 50-55%), 6.2m³ of leached filtrate, lithium content 6.5g / L, aluminum content 5.4g / L. Adjust the pH of the leaching solution to 1.5-1.6, add 311kg of sodium fluoride (purity 95%), control the temperature at 60℃, stir and react for 1h, filter to obtain 525kg of aluminum removal slag and 6m³ of purified liquid, the aluminum content of the purified liquid is 0.131g / L. Slowly add excess 27.5% hydrogen peroxide under stirring conditions to the purified liquid, and react to synthesize dihydrate iron phosphate. The synthetic mother liquor is lithium sulfate solution 1, and the lithium concentration is 5.7g / L. Add 1000kg water and 300kg sulfuric acid to the aluminum slag for stirring leaching, the leaching temperature is 85℃, the leaching time is 2h, the end point pH is 0.6, calcium carbonate is added to adjust the pH to 5-5.5 for defluorination, and the leached slag and lithium sulfate solution 2 are obtained by filtration and washing, with a lithium concentration of 4.2g / L. Under the mixing conditions of lithium sulfate solution 1 and lithium sulfate solution 2, sodium hydroxide is added to adjust the pH to 10 for weight removal, and then the solution is injected into the MVR concentration system, and the lithium concentration of the liquid is 18g / L. Prepare 250g / L sodium carbonate solution according to the lithium carbonate equivalent, slowly add it to the concentrated lithium sulfate solution, control the temperature at 92℃, continue to react for 30min after the sodium carbonate solution is added, and the slurry is centrifuged and washed to obtain lithium carbonate. The purity of lithium carbonate is 99.41%, which meets the industrial grade requirements.

Claims

1. A method for applying fluorine-containing waste slag from electrolytic aluminum, characterized in that: The method comprises the following steps: (1) First prepare a sodium hydroxide solution, add the fluorine-containing waste slag powder into the solution for activation for 1-2 hours, filter to obtain the activated slag and filtrate, measure the moisture and dry basis fluorine content of the activated slag, and reuse the filtrate to activate the next batch of overhaul slag; (2) The lithium iron phosphate battery powder is completely dissolved in sulfuric acid, and the carbon powder and leachate are obtained by filtration; (3) Control the pH of the leaching solution between 1.5 and 2 by adding sodium carbonate, and add a certain amount of activated slag for stirring to remove aluminum; (4) The aluminum removal slurry is filtered to obtain a purified liquid and aluminum removal slag. An oxidant is added to the purified liquid under certain conditions to prepare iron phosphate. The synthetic mother liquor of iron phosphate is mainly an acidic lithium sulfate solution 1 with a lithium concentration of 5-8 g / L; (5) The aluminum slag is then leached with sulfuric acid, and the fluorine is removed with calcium carbonate. The lithium sulfate solution 2 and tailings are obtained by filtration. The lithium concentration of the lithium sulfate solution 2 is 4-7 g / L, and the tailings are sent to the cement plant as cement raw materials; (6) The lithium sulfate solution 1 and the lithium sulfate solution 2 are mixed and impurities are removed again. The impurity-removed purified liquid enters the MVR concentration system to separate sodium sulfate salt and lithium sulfate solution with a lithium concentration of 15-20 g / L; (7) A certain amount of sodium carbonate is added to the lithium sulfate solution to stir and precipitate lithium. The lithium carbonate product and the sodium sulfate solution containing lithium are obtained by filtration. The sodium sulfate solution containing lithium is returned to the MVR for further concentration.

2. The method for applying the fluorine-containing waste slag from electrolytic aluminum according to claim 1, characterized in that The fluorine-containing waste slag is one or a mixture of electrolytic aluminum overhaul slag, carbon slag, and electrolyte, with a lithium content of 1-3%, a fluorine content of 20-40%, an aluminum content of 8-15%, and a fineness of more than 150 meshes.

3. The method for applying the fluorine-containing waste slag from aluminum electrolysis according to claim 1, characterized in that The fluorine-containing waste residue activation solid-liquid ratio is 1:(1-3), the sodium hydroxide concentration is 5-15%, the activation temperature is 60-80° C., and the activation time is 1-3 hours.

4. The method for applying fluorine-containing waste slag from aluminum electrolysis according to claim 1, characterized in that The solid-liquid ratio of lithium iron phosphate battery powder leaching is 1:(3-5), the leaching endpoint pH is 0.5-1.5, the leaching time is 2-5h, and the leaching temperature is 40-80℃.

5. The method for applying the fluorine-containing waste slag from aluminum electrolysis according to claim 1, characterized in that The amount of aluminum added to the activated slag for aluminum removal is based on the fluorine-aluminum ratio. The mass ratio of total fluorine in the activated slag to total aluminum in the battery powder leachate is (3-5):

1. The typical aluminum concentration in the leachate is 3-5g / L, which is less than 0.15g / L after aluminum removal. The aluminum removal efficiency is greater than 95%.

6. The method for using fluorine-containing waste slag from aluminum electrolysis according to claim 1, characterized in that The solid-liquid ratio of sulfuric acid leaching to remove aluminum slag is 1:(2-4), the leaching end point pH is 0.5-1.5, the leaching time is 2-5h, and the leaching temperature is 60-100℃.

7. The method for using fluorine-containing waste slag from aluminum electrolysis according to claim 1, characterized in that The temperature of the sodium carbonate lithium precipitation process is 90-95°C, and 200-300g / L of sodium carbonate solution is added. The obtained lithium carbonate meets industrial grade standards.